Hubungan antara Ekspresi Hsp 27 dan Hsp 70 Dengan Derajat Diferensiasi dan Angka Ketahanan Hidup Dua Tahun pada Penderita Kanker Endometrium Tipe I Pasca-Pembedahan di RSUD Dr. Soetomo - YULIATI, INDRA; ASKANDAR, BRAHMANA; FAUZIAH, DYAH (Indonesian Journal of Cancer, 2015)
This research was performed to know the relation between Hsp 27 and Hsp 70 expressions with degree of differentiation and two years survival rate in endometrial cancer type I that has undergone surgery in Dr. Soetomo Hospital, Surabaya. Methods: using observational analysis with retrospective Cohort study design to the endometrial cancer type I patients that had undergone surgery in Dr. Soetomo Hospital. As many as 30 subjects were examined, with dependent variable: Hsp 27 and Hsp 70 expressions and Dependent Variable: the type of endometrial cancer differentiation and 2 years survival rate of the endometrial cancer type I patients. In this research, 30 patients with endometrial cancer type I that had undergone surgery were obtained, with well differentiation (grade I) for 20 samples (66.7%), moderate differentiation (grade II) for 3 samples (10%) and poor differentiation (grade III) accounts for 7 samples (23.3%). Positive results for Hsp 27 are 13 samples, while negative Hsp 27 results are 17 samples. From the analysis, correlation coefficient is -0.218 and p value 0.248 (p > 0.05). Samples with positive Hsp 70 results are 19 (63.3%) and negative Hsp 70 results are 11 samples (36.7%), with correlation coefficient -0.099 and p value 0.603 (p > 0.05). Overall survival rate for Hsp 27 is 22.5 months (log rank 0.066), survival rate 1 year for positive Hsp 27 are 100%, and negative Hsp 27 are 88.2%, while in Hsp 70, the overall survival rate is 22.5 months (log rank 0.076), survival rate 1 year for positive Hsp 70 are 100% and negative Hsp 70 are 81.8%. There are no significant relations between Hsp 27 expression with tumor cells differentiation (grade) and the 2 years survival rate of the endometrial cancer type I patients. And also there are no significant relations between Hsp 70 expressions with tumor cells differentiation (grade). 2 years survival rate of the endometrial cancer type I with positive or negative Hsp expressions are not significantly correlated. And there are no significant relations between 2 years survival rate of the endometrial cancer type I with the cells differentiation degree.Keywords: Hsp 27, Hsp 70, differentiation degree, survival rate, endometrial cancer typeI.Â ABSTRAKPenelitian ini dilakukan untuk mengetahui hubungan antara ekspresi Hsp 27 dan Hsp 70 dengan derajat diferensiasi dan angka ketahanan hidup dua tahun pada penderita kanker endometrium tipe I pasca-pembedahan di RSUD Dr. Soetomo, Surabaya. Penelitian ini menggunakan penelitian analitik observasional dengan rancangan studi kohort retrospektif terhadap penderita kanker endometrium tipe 1 yang telah dilakukan pembedahan di RSUD Dr. Soetomo, Surabaya, sebanyak 30 subjek. Sebagai variabel bebas: ekspresi Hsp 27 dan Hsp 70. Variabel tergantung: jenis diferensiasi kanker endometrium dan angka ketahanan hidup 2 tahun penderita kanker endometrium tipe 1. Pada penelitian ini, didapatkan kanker endometrium tipe I yang telah dilakukan pembedahan sebanyak 30 penderita. Didapatkan sediaan dengan diferensiasi baik (grade I ) sebanyak 20 (66,7%), diferensiasi sedang (grade 2) 3 sediaan (10%), dan diferensiasi buruk (grade 3) sebanyak 7 sediaan (23,3%). Dengan ekspresi Hsp 27 positif sebanyak 13 sediaan, sedangkan dengan ekspresi Hsp 27 negatif sebanyak 17 sediaan. Dari hasil analisis didapatkan koefisienkorelasi -0,218 dan p value 0,248 (p>0,05). Sediaan dengan ekspresi Hsp 70 positif sebanyak 19 (63,3%), sedangkan Hsp 70 negatif 11 sediaan (36,7%), dengan koefisien korelasi -0,099 dan p value 0,603 (p > 0,05). Dengan overall survival sebesar 22,5 bulan (log rank 0,066), survival rate 1 tahun untuk Hsp 27 positif sebesar 100% dan Hsp 27 negatif sebesar 88,2%. Sedangkan pada Hsp 70, overall survival 22,5 bulan (log rank 0,076) dan survival rate 1 tahun untuk Hsp 70 positif sebesar 100% dan Hsp 70 negatif sebesar 81,8%. Tidak ada hubungan yang bermakna antara ekspresi Hsp 27 dengan diferensiasi sel tumor (grade) dan angka ketahanan hidup dua tahun penderita kanker endometrium tipe I. Tidak didapatkan hubungan yang bermakna juga antara ekspresi Hsp 70 dengan diferensiasi sel tumor (grade) dan angka ketahanan hidup dua tahun penderita kanker endometrium tipe I dengan ekspresi Hsp 70 positif ataupun negatif. Tidak ada hubungan antara angka ketahanan hidup dua tahun penderita kanker endometrium tipe I dengan derajat diferensiasi sel (grade).Â Kata Kunci: Hsp 27, Hsp 70, derajat diferensiasi, angka ketahanan hidup, kanker endometrium tipe 1.